2004
DOI: 10.1128/mcb.24.9.3623-3632.2004
|View full text |Cite
|
Sign up to set email alerts
|

SUMO Modification of Heterogeneous Nuclear Ribonucleoproteins

Abstract: Small ubiquitin-related modifiers (SUMOs) are proteins that are posttranslationally conjugated to other cellular proteins, particularly those that localize and function in the nucleus. Enzymes regulating SUMO modification localize in part to nuclear pore complexes (NPCs), indicating that modification of some proteins may occur as they are translocated between the nucleus and the cytoplasm. Substrates that are regulated by SUMO modification at NPCs, however, have not been previously identified. Among the most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 45 publications
4
86
0
1
Order By: Relevance
“…With the long distances that mRNAs and RNA-binding proteins must travel in neurons, sumoylation may provide a means to recycle some proteins to the nucleus by targeting these proteins for retrograde transport. Sumoylation has recently been demonstrated for a few RNAbinding proteins (19)(20)(21)(22). Sumoylation of hnRNP C decreases its nucleic acid binding (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the long distances that mRNAs and RNA-binding proteins must travel in neurons, sumoylation may provide a means to recycle some proteins to the nucleus by targeting these proteins for retrograde transport. Sumoylation has recently been demonstrated for a few RNAbinding proteins (19)(20)(21)(22). Sumoylation of hnRNP C decreases its nucleic acid binding (21).…”
Section: Discussionmentioning
confidence: 99%
“…Sumoylation has recently been demonstrated for a few RNAbinding proteins (19)(20)(21)(22). Sumoylation of hnRNP C decreases its nucleic acid binding (21). Sumoylation at K41 could affect La's interaction with target mRNAs, because this residue lies within the La motif, and deletions of the La motif alter La's affinity for target RNAs (3).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nuclear sumoylation of Dictyostelium Mek1 is responsible for its movement to the cytoplasm (37), and mutation of lysine 99 of the TEL protein leads to increased levels of this protein in the nucleus, suggesting a possible role for sumoylation in its nuclear export (38). In addition, sumoylation of heterogeneous nuclear ribonucleoproteins M and C has been proposed to function as a regulator of conformational changes that may influence nucleocytoplasmic transport of these protein complexes (39).…”
mentioning
confidence: 99%
“…Dendritic cells are the key antigen-presenting cells which process the antigen and initiate immune response; we expected that the study of this novel ubiquitin-like molecule could contribute to our knowledge of the mechanism of immune response. Multiple alignment analysis of DULP, ubiquitin and other ubiquitin-like proteins showed that ubiquitin, NEDD8, UCRP and Sentrin-1 (SUMO-1) all had a diglycine motif situated either directly at the carboxyl terminus of the UBL or within the sequence of a UBL precursor, which is required for conjugation formation (15)(16)(17)(18), but the ubiquitin domain in DULP did not possess the highly conserved C-terminus Gly-Gly for attachment to -amino group of substrate protein's Lys residues. Moreover, the sequence analysis also showed three conserved Lys residues within ubiquitin: Lys29, Lys48 and Lys63.…”
Section: Discussionmentioning
confidence: 99%